Aktivitas Antibakteri Ekstrak Etanol Buah Wualae (Etlingera elatior (JACK) R.M. Smith) - Wahyuni Wahyuni; Fadhliyah Malik; Andryani Ningsih; Wa Ode Sitti Zubaydah; Sahidin Sahidin (STIFA Makassar, 2018)
Wualae (Etlingera elatior (Jack) R.M. Smith) belonging to Zingeberaceae that spread in South East Sulawesi, empirically used as staple and treatment. The aim of this research to determine the antimicrobial potential of ethanol extract fruit of E. elatior against gram positive (Staphylococcus aureus ATCC 25923 and Bacillus subtilis FNCC 0060), and gram negative (Pseudomonas aeruginosa ATCC 27853 and Salmonella enterica ATCC 14028) using cup-plate method. The antimicrobial activity based on the diameter of inhibition zone. The result shows that extract more potential to inhibit gram positive than gram negative while the highest inhibition illustrate by concentration of 20 mg/mL (inhibition zone= 5 mm). In conclusion, the extract of E. elatior no potent as antimicrobial candidate (category= weak).